Characterization and genetic divergence of araçá-boi based on physicochemical and colorimetric traits of fruits - Dieimes Bohry (Revista de Ciências Agrárias, 2018)
The araçá-boi (Eugenia stipitata McVaugh), a native fruit from the Amazonian Forest, has great potential for fruit pulp production. Araçá-boi cultivation could diversify the incomes of small farmers and contribute to food security. However, little is known about the physicochemical, physiological, and agronomic aspects of araçá-boi, making its cultivation and expansion limited. This study aimed to characterize the physicochemical and colorimetric traits of fruits of araçá-boi and to access the genetic diversity among the studied accessions. Eight fruits of 33 accessions were collected for evaluation. The experiment was carried out at the Instituto Federal do Espírito Santo – Campus Itapina, located in Colatina-ES, in the year of 2015. Seven physicochemical traits and eight chromaticity parameters of fruits were measured. Grouping methods, such as Tocher optimization, hierarchical grouping, and principal component analysis (PCA), were applied to study the genetic diversity. It was observed phenotypic variability for all the evaluated traits. The three grouping methods were efficient for representing the genetic divergence among the accessions. The accessions 28 and 25 are interesting for clonal seedlings, for presenting good averages of fruit mass (FM), pulp mass (PM) and a relatively high total soluble solid (TSS) content. To develop a base population, besides accessions 28 and 25, the accession 33, which presented the highest TSS and accession 1 or 21, with high averages of FM and PM should be included in crossings to obtain a base population aiming to start a breeding program of araçá-boi.